Baking with Dorie : sweet, salty & simple - Greenspan, Dorie (Houghton Mifflin Harcourt, 2021)
"From James Beard Award-winning and NYT best-selling author Dorie Greenspan, a baking book of more than 150 exciting recipes. Say "Dorie Greenspan" and think baking. The renowned author of thirteen cookbooks and winner of five James Beard and two IACP awards offers a collection that celebrates the sweet, the savory, and the simple. Every recipe is signature Dorie: easy-beginners can ace every technique in this book-and accessible, made with everyday ingredients. Are there surprises? Of course! You'll find ingenious twists like Berry Biscuits. Footlong cheese sticks made with cream puff dough. Apple pie with browned butter spiced like warm mulled cider. A s'mores ice cream cake with velvety chocolate sauce, salty peanuts, and toasted marshmallows. It's a book of simple yet sophisticated baking. The chapters are classic: Breakfast Stuff Cakes Cookies Pies, Tarts, Cobblers and Crisps Two Perfect Little Pastries Salty Side Up. The recipes are unexpected. And there are "Sweethearts" throughout, mini collections of Dorie's all-time favorites. Don't miss the meringue Little Marvels or the Double-Decker Caramel Cake. Like all of Dorie's recipes, they lend themselves to being remade, refashioned, and riffed on"--